2019
DOI: 10.1002/asia.201801561
|View full text |Cite
|
Sign up to set email alerts
|

A Z‐Scheme Polyimide/AgBr@Ag Aerogel with Excellent Photocatalytic Performance for the Degradation of Oxytetracycline

Abstract: An ovel Z-schemep olyimide (PI)/AgBr@Aga erogel photocatalyst has been successfully synthesized by combining an in situ precipitation method and as upercritical drying method. The as-prepared PI/AgBr@Ag-50 (50 wt % AgBr@Ag in PI/AgBr@Ag) aerogel photocatalyst exhibited excellent photocatalytic activity foro xytetracycline degradation with ar ate constant of 0.025 min À1 ,w hich was 6.9 and 2.6 times higher than that of the PI aerogel or the AgBr@Ag nanoparticles, respectively.M ore significantly,t he PI/ AgBr@… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 69 publications
(73 reference statements)
0
6
0
Order By: Relevance
“…However, melamine, phenol, and other copolymerization modifiers are petrochemical products, which could cause serious environmental pollution and overload the resource burden as they are widely used [ 18 , 19 , 20 ]. The seriously environmental problems are against green and sustainable development [ 21 , 22 , 23 ]. The second problem is that: much flour or starch was used to adjust the initial viscosity and rheological behavior of the resin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, melamine, phenol, and other copolymerization modifiers are petrochemical products, which could cause serious environmental pollution and overload the resource burden as they are widely used [ 18 , 19 , 20 ]. The seriously environmental problems are against green and sustainable development [ 21 , 22 , 23 ]. The second problem is that: much flour or starch was used to adjust the initial viscosity and rheological behavior of the resin.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its physical and chemical particularity, it has been more and more widely used in various fields [ 45 , 46 ]. For example, the HNTs with curly tubular structure could be used as an efficient adsorbent especially in the adsorption area [ 22 , 47 ]. Zhao studied the effect of temperature, pH, and initial concentration on the adsorption of methylene blue by HNTs.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al reported PI-based aerogels for the degradation of oxytetracycline under visible-light irradiation. 84 A PI/silver bromide (AgBr)@Ag composite aerogel was prepared as a photocatalyst by dispersing AgBr@Ag nanoparticles uniformly on a PI aerogel (Fig. 7(e)).…”
Section: The Structure and Topology Of Pimentioning
confidence: 99%
“…However, the powder samples are difficult to recycle. Recently, our team has been focusing on research into PI aerogel photocatalysts, which possess high specific surface area and abundant pore structure compared with the conventional PI powder photocatalysts [10,11]. Apart from that, the adsorption capacity of CO 2 over a photocatalyst will influence the CO 2 reduction activity greatly.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, the CB energy of PI aerogel is 1.3∼1.7 eV (versus normal hydrogen electrode (NHE)), which is favorable for CO 2 reduction because of the higher reduction activity of photo-generated electrons [10,11]. However, on the one hand, the VB position of PI aerogel cannot stretch across the reaction potential of H 2 O oxidation and so cannot accelerate the reduction of CO 2 (CO 2 -COOH * -CO) [15].…”
Section: Introductionmentioning
confidence: 99%